"Alas … my sickness becomes my family's burden": A nested qualitative study on the experience of advanced breast cancer patients across the disease trajectory in Indonesia. (June 2022) - Prabandari, Yayi Suryo; Hartanti, Wika; Syafriani,; Widiastuti, Mentari; Witaningrum, Riani; Hutajulu, Susanna Hilda; Allsop, Matthew John
Abstract: Introduction: Limited research exists exploring the experience of living with advanced breast cancer in Indonesia. We sought to explore the narratives of women with breast cancer across the illness trajectory to understand their experiences from diagnosis to accessing and undergoing cancer treatments to inform the development of cancer care. Methods: A nested, exploratory study adopting a qualitative approach. We conducted in-depth face-to-face interviews with women living with advanced breast cancer in Yogyakarta, Indonesia. We purposively sampled participants by age, education and marital status. All interviews were transcribed verbatim with thematic analysis used to identify, analyse and report patterns and themes within the data. Findings: Four main themes were derived: 1) Early experiences, prior to accessing health care; 2) Navigating the system to access treatment; 3) Enduring chemotherapy and advancing disease, with crucial family support; 4) Seeking normalcy and belief in treatment. From initial symptoms through to undergoing treatments, the experience of participants was punctuated by barriers and challenges. Discussion: Presentation delays were driven by dismissing initial symptoms, seeking alternative medicines, and fear of surgery. Access to healthcare required participants to contend with long-distance travel to facilities, tiered and convoluted referral processes, and adverse effects and financial impact of treatments. Individual determination, belief in God, and the role of families were critical throughout the disease trajectory. Adopting a focus across the disease trajectory facilitated the identification of enduring and persistent challenges to care delivery that can inform targeted development and optimisation of care delivery for women with breast cancer. Highlights: This is the first exploration of breast cancer patients' experiences across the disease trajectory in Indonesia. Patients endure convoluted referral processes, long distance travel, and commonly experience financial burden and severe side effects. Family play a critical role in providing physical, psychological and financial support during treatment. Healing is understood as resuming normalcy in daily activity, mobility and independence rather than cure. Focusing across the disease trajectory facilitated the identification of enduring and persistent challenges to care delivery that can inform targeted development of care delivery.